Association Between GSDMB Gene Polymorphism and Cervical Cancer in the Northeast Chinese Han Population - Li, Songxue; Li, Xiaoying; Zhang, Shuang; Feng, Yanan; Jia, Tianshuang; Zhu, Manning; Fang, Lei; Gong, Liping; Dong, Shuang; Kong, Xianchao; Wang, Zhenzhen; Sun, Litao (Frontiers in Genetics, 2022)
Objective: The purpose of this study was to investigate the relationship between GSDMB gene polymorphism and genetic susceptibility to cervical cancer in Han population in Northeast China. Methods: In this case-control study, the genotypes and alleles of rs8067378 in GSDMB gene were analyzed by multiplex polymerase chain reaction (PCR) and next-generation sequencing methods in 482 cervical cancer (CC) patients, 775 cervical squamous intraepithelial lesions (SIL) patients and 495 healthy women.. The potential relationships between the SNP of GSDMB gene with SIL and CC were analyzed by multivariate logistic regression analysis combined with 10000 permutation tests. Results: In the comparison between SIL group with controls group, the genotype and allele distribution frequencieies of rs8067378 SNP of GSDMB gene were statistically significant (p = 0.0493, p = 0.0202, respectively). The alleles distribution frequencieies of rs8067378 were also statistically significant in the comparison between high-grade cervical squamous intraepithelial lesions (HSIL) and low-grade cervical squamous intraepithelial lesions (LSIL) group with controls group (respectively, p = 0.0483, p = 0.0330). Logistic regression analysis showed that after adjusting for age, the rs8067378 SNP of GSDMB gene was significantly associated with the reduced risk of SIL under the dominant model (p = 0.0213, OR = 0.764, CI = 0.607-0.961) and the additive model (p = 0.0199, OR = 0.814, CI = 0.684-0.968), its mutant gene G may play a role in the progression of healthy people to LSIL and even HSIL as a protective factor. However, there was no significant association between cervical cancer and its subtypes with controls group (p > 0.05). After 10,000 permutations, there was still no correlation that has provided evidence for the accuracy of our study. Conclusion: The results of this study showed that the rs8067378 single nucleotide polymorphism of GSDMB gene may reduce the risk of SIL and protect the susceptibility to cervical precancerous lesions in Northeast Chinese Han population, but it has no significant correlation with the progression of cervical cancer.